Coordinated Nanoscale Compositional and Oxidation State Measurements of Lunar Space‐Weathered Material. Issue 8 (18th August 2018) - Burgess, K. D.; Stroud, R. M.
Abstract: Space weathering on airless bodies includes a number of processes, such as micrometeorite impacts and solar wind bombardment, which leads to a variety of microscale to nanoscale alteration features, including vapor deposited layers on grain and rock surfaces and creation of nanophase opaque inclusions. The nanophase inclusions cause reddening and darkening of the visible to near‐infrared spectra of space weathered material, features associated with increasing space exposure of many airless body regoliths. On the Moon, most nanophase inclusions are metallic iron (npFe 0 ), but recent work using aberration‐corrected scanning transmission electron microscopy and electron energy loss spectroscopy has provided evidence of oxidized nanoparticles in space weathered lunar soil grains. We examined three different lunar soils in order to confirm the finding of oxidized nanophase inclusions and to provide detailed elemental and mineralogical information about the surrounding material. Our data show that substrate and rim composition are key factors in determining whether highly localized oxidation occurs; for example, nanophase inclusions in rims on low Fe substrates are more prone to oxidation. Detailed understanding of the phases and features present in these samples is necessary for the correct interpretation of remotely sensed data as well as extrapolation from processes on the lunar surface to those on other airless bodies. Plain Language Summary: The Moon and asteroids are being constantly altered by interactions with the space environment, a process known as space weathering. These interactions, such as with solar wind ions and micrometeoroids, can be studied by examining samples from the Moon and analyzing the nanoscale features present in surface coatings or rims on small lunar dust grains. Using techniques such as energy dispersive X‐ray spectroscopy and electron energy loss spectroscopy in the scanning transmission electron microscope, we are able to image and measure the composition and oxidation state of the nanoscale inclusions and layers in these rims. These data provide evidence of complex material interactions, such as formation of metallic iron inclusions at a variety of sizes contained within specific sublayers, and oxidation to magnetite of some of those inclusions. From this information, we can better interpret spacecraft and telescopic data of the Moon and asteroids that can be significantly influenced by space weathering and the presence of nanoscale inclusions. We can also compare these data to samples that have been experimentally space weathered in the laboratory using pulsed laser or ion irradiation in order to gain a better understanding of the conditions necessary to create observed features. Key Points: Composition and iron valence state information was acquired for lunar space weathered rims using scanning transmission electron microscopy Some nanophase Fe‐rich inclusions and rims are oxidized and are associated with low‐Fe grains The amount of oxidized material is small but could affect optical properties or other measurements